Way of the Wolf - Grylls, Bear (Random House Group, 2009)
A fatal plane crash. A frozen wilderness. The world's youngest survival expert is in trouble again$1! = (BBeck Granger must find help across the mountains - but even if he survives the deadly cold, can he escape the hungry wolf that is on his trail?...s
Keywords: Adventure; Juvenile Fiction